Degradation of Fibrinogen by Proteolytic Enzymes - Sanchez-Avalos, J; Miller, S. P (Thrombosis and Haemostasis, 1968)
Fibrinogen was subjected to enzymatic degradation by streptokinase-activated plasminogen (plasmin). There was a rapid split of the molecule into large polypeptide components. Four components were seen by electrophoresis in acrylamide gel. Two major components (D and E) were identified by Immunoelectrophoresis and immune diffusion. In addition, a minor component which arose from the slow component and is called D’ was seen.Fibrin degradation yielded a slow component that was identical with the slow component of fibrinogen, but the fast component (E) of fibrin was different from that of fibrinogen.Degradation of fibrinogen by trypsin, chymotrypsin and papain was not mediated through the plasminogen-plasmin system. The initial action of these enzymes yielded fragments which were immunologically identical and electrophoretically similar to those of plasmin, but subsequent action of chymotrypsin led to further degradation of the slow component, while the fast component was subsequently destroyed by papain.The two main components (D and E) could be identified in the plasma and serum of patients suffering from fibrinolytic disorders. The components were immunologically identical with the components produced in vitro by proteolytic enzymes.